High-performance and tailorable pressure sensor based on ultrathin conductive polymer film - Shao, Qi (2014)
A highly sensitive and tailorable pressure sensor is designed based on the variation of contact resistance between an Au covered micropillar array and a conductive polymer film. The sensitivity of such pressure sensors can be tuned from 0.03 kPa−1 to 17 kPa−1 at pressures less than 1 kPa, and a limit of detection of 2 Pa has been demonstrated.